EVALUASI KEBIJAKAN BADAN KESATUAN BANGSA DAN POLITIK PROVINSI BENGKULU DALAM PELAKSANAAN PEMANTAPAN KEBANGSAAN (Studi Pada Bidang Pemantapan Kebangsaan) - Alexsander; Stevani, Risa; Aprianty, Henny; Noviyanto, Hernowo (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2024)
This investigation was carried out with the aim of assessing the basis of the Bengkulu Province National and Political Unity Agency in its efforts to strengthen national integration and integration. The study method used is a qualitative study. The data in this investigation was obtained from primary and secondary sources. The data collection methods used were observation, interviews and documentation. Data analysis was carried out by means of data reduction, data presentation, and inference/validation procedures. The results of the study show that: 1) The basis of the Bengkulu Province National and Political Unity Agency in strengthening national unity and integrity has been implemented well and responsibly, this can be seen from the results of the study which is based on information obtained from informants. 2) Assessment of the policies of the Bengkulu Province National and Political Agency in strengthening national unity and integrity has gone well, in accordance with public policy indicators which include: a) Input Indicators, b) Process Indicators, c) Output Indicators, and d) Result Indicators . 3) The employees have also tried their best to continue to improve the basis of the Bengkulu Province National and Political Unity Agency in strengthening national unity and unity.